Procedures For Resolving Islamic Economic Disputes In Indonesia - Nur Raihan; Try Widiyono (LP2M IAIN Palopo, 2025)
This research is titled Efforts to Resolve Sharia Economic Disputes at the Central Jakarta Religious Court through a case study of Decision No. 634/Pdt.G/2024/PA. JP. The purpose of this research is to delve deeper into the procedures and basis for judges' considerations in deciding case number 634/Pdt.G/2024/PA. JP at the Central Jakarta Religious Court. Then to find out the views of Sharia Economic Law on the basis of consideration by the Central Jakarta Religious Court Judge in deciding a case that declares the validity and value of Defendant II's non-Muslim property as a guarantee for the payment of obligations from Defendant I. This research uses a normative method with a juridical approach, examining laws and regulations, court decisions, and related literature. Based on the research method, a study was produced that revealed that in principle the procedure for resolving sharia economic disputes at the Central Jakarta Religious Court is the same as other courts in Indonesia, starting from the registration of the case by the plaintiff, the examination of the file and the determination of the panel of judges, the summoning of the parties (plaintiff and the defendant), the first hearing and peace efforts (mediation), the reading of the lawsuit, the defendant's answer (exception and subject matter), Replica of the plaintiff, duplicate of the plaintiff, proof, conclusion of the parties, deliberation of the panel of judges, reading of the decision and legal remedies if any. However, there are separate rules in the Central Jakarta Religious Court such as divorce. The final conclusion of this study is that the settlement of sharia economic disputes at the Central Jakarta Religious Court has been carried out in accordance with positive legal procedures and sharia principles, although there are still some challenges in its implementation.